Molecular Identification of Broomrape Species from a Single Seed by High Resolution Melting Analysis - Rolland, Mathieu; Dupuy, Aurélie; Pelleray, Aude; Delavault, Philippe (Frontiers in Plant Science, 2016)
Broomrapes are holoparasitic plants spreading through seeds. Each plant produces hundreds of thousands of seeds which remain viable in the soils for decades. To limit their spread, drastic measures are being taken and the contamination of a commercial seed lot by a single broomrape seed can lead to its rejection. Considering that broomrapes species identification from a single seed is extremely difficult even for trained botanists and that among all the described species, only a few are really noxious for the crops, numerous seed lots are rejected because of the contamination by seeds of non-noxious broomrape species. The aim of this study was to develop and evaluate a High Resolution Melting assay identifying the eight most noxious and common broomrape species (P. aegyptiaca, O. cernua, O. crenata, O. cumana, O. foetida, O. hederae, O. minor, and P. ramosa) from a single seed. Based on trnL and rbcL plastidial genes amplification, the designed assay successfully identifies O. cumana, O. cernua, O. crenata, O. minor, O. hederae, and O. foetida; P. ramosa and P. aegyptiaca can be differentiated from other species but not from each other. Tested on 50 seed lots, obtained results perfectly matched identifications performed by sequencing. Through the analysis of common seed lots by different analysts, the reproducibility of the assay was evaluated at 90 %. Despite an original sample preparation process it was not possible to extract enough DNA from some seeds (10% of the samples). The described assay fulfils its objectives and allows an accurate identification of the targeted broomrape species. It can be used to identify contaminants in commercial seed lots or for any other purpose. The assay might be extended to vegetative material.